ANALYSIS OF EMOTIONAL EXHAUSTION THROUGH DOWNSIZING WITH JOB SATISFACTION AS MEDIATION - Clement, Nathaniel; Adiputra, I Gede (Graduate Program of Universitas Tarumanagara, 2023)
Nowadays, many tech companies are on a downward trend. This can be referred to as a tech bubble burst. This makes it very difficult for companies, especially those in the e-commerce industry, financially. These companies are constantly looking for ways to make efficiencies in order to save costs and streamline the company. There are many ways to do that, but the most commonly used is downsizing. Downsizing is a way of efficiency by removing unnecessary employees to avoid unnecessary costs. Although downsizing is effective in saving costs, there are some negative effects of downsizing, namely its effect on emotional exhaustion and job satisfaction of the remaining employees in the company or can be said to be layoff survivors. Emotional exhaustion can be interpreted as emotional exhaustion towards their work while job satisfaction is the feeling of satisfaction that a person has when doing their job. The purpose of this study is to determine and analyze the effect of downsizing on emotional exhaustion and job satisfaction of employees working in the e-commerce industry in Indonesia. This study uses quantitative research methods with a cross sectional approach and non-probability sampling techniques with data obtained by means of questionnaires distributed to 180 respondents. The results of this study Downsizing has a significant effect on emotional exhaustion, Downsizing has a significant effect on job satisfaction, Job Satisfaction has a significant effect on emotional exhaustion, Job Satisfaction can mediate the effect of downsizing on emotional exhaustion.